Isolation and Identification Some of microbial causes for dental caries - Rana jalal; Bari Lateef; Vian Ibrahim (Tikrit Journal of Pure Science)
This study was conducted for the isolation of some microbial cause tooth decay and determine the risk factors related to caries. 91 sample collected from teeth (plaques or swabs from dental caries), (41) sample from children  (6-14) years and (50) sample from adult (15-70) years, subdivided into (30) sample associated with risk factors and (20) sample without risk factors. A total of 61 isolates were identified in which 38 isolates (41.75%) were S. aureus, 16 isolates (17.58%) were Streptococcus spp. and 7 isolates (7.69%) were identified as Candida albicans.